Evidence of a clinically significant drug‐drug interaction between cannabidiol and tacrolimus. Issue 10 (21st May 2019) - Leino, Abbie D.; Emoto, Chie; Fukuda, Tsuyoshi; Privitera, Michael; Vinks, Alexander A.; Alloway, Rita R.
Abstract : Cannabidiol (CBD), a major purified nonpsychoactive component of cannabis with anticonvulsant properties, was approved by the U.S. Food and Drug Administration (FDA) in June 2018 as an adjuvant treatment for refractory epilepsy (Epidiolex; GW Pharmaceuticals). CBD is metabolized by cytochrome P450 (CYP)3A4 and CYP2C19 with a growing body of evidence suggesting it is also a potent inhibitor of these pathways. We report for the first time a significant drug‐drug interaction between the purified CBD product and tacrolimus. A participant in a CBD clinical trial for epilepsy who was also receiving tacrolimus showed an approximately 3‐fold increase in dose‐normalized tacrolimus concentrations while receiving 2000‐2900 mg/day of CBD. Our report delineates an important concern for the transplant community with the increasing legalization of cannabis and advent of an FDA‐approved CBD product. Larger studies are needed to better understand the impact of this drug‐drug interaction in solid organ transplant recipients. Abstract : A case of a clinically significant drug interaction with a pharmaceutical‐grade cannabidiol product and tacrolimus suggests caution when using the combination.